2011
DOI: 10.3945/jn.111.139378
|View full text |Cite
|
Sign up to set email alerts
|

Food Security of Older Adults Requesting Older Americans Act Nutrition Program in Georgia Can Be Validly Measured Using a Short Form of the U.S. Household Food Security Survey Module

Abstract: Food security is a newly recommended outcome measure for the Older Americans Act Nutrition Program (OAANP); however, it is unknown how best to evaluate the need for this program and assess its impact on a large scale. Therefore, we measured food security in all new OAANP participants and waitlisted applicants in Georgia between July and early November, 2008 (n = 4731) with the self-administered mail survey method used in the ongoing Georgia Performance Outcomes Measures project. We used a modified 6-item U.S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 13 publications
0
43
0
1
Order By: Relevance
“…Our findings suggest that behaviors related to cognitive restraint and emotional eating that need to be addressed include consciously eating less than desired, consciously having to avoid ''stocking up'' on tempting foods, avoiding foods because they are fattening, eating when anxious, and overeating when feeling anxious, lonely, or ''blue.'' The high prevalence of food insecurity in this sample as well as in several other studies of older adults accessing Georgia's OAA programs (33,35) adds an additional level of complexity in addressing obesity and weight management in these congregate meal participants. The expertise of dietitians, mental health experts, physicians, and other health care professionals could help provide older adults with the necessary motivation and tools to first identify inappropriate eating and activity behaviors and to learn new approaches to deal with these learned behaviors.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings suggest that behaviors related to cognitive restraint and emotional eating that need to be addressed include consciously eating less than desired, consciously having to avoid ''stocking up'' on tempting foods, avoiding foods because they are fattening, eating when anxious, and overeating when feeling anxious, lonely, or ''blue.'' The high prevalence of food insecurity in this sample as well as in several other studies of older adults accessing Georgia's OAA programs (33,35) adds an additional level of complexity in addressing obesity and weight management in these congregate meal participants. The expertise of dietitians, mental health experts, physicians, and other health care professionals could help provide older adults with the necessary motivation and tools to first identify inappropriate eating and activity behaviors and to learn new approaches to deal with these learned behaviors.…”
Section: Discussionmentioning
confidence: 93%
“…We used a longitudinal study design implementing 3 repeated surveys at 4-month intervals, asking participants about their experiences with FI and CRN in the past 30 days of survey completion. By using the validated modified version of the 6-item HFSSM, we were able to collect accurate and comparable FI data while reducing the response burden in our vulnerable older adult sample (28). Although not systematically validated, the CRN measure used in this study accessed key CRN behaviors most frequently reported in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…, Swindale & Bilinsky , Lee et al . ). Various measurements have been developed emphasising different aspects of food security in terms of food availability, affordability, utilisation and accessibility from geographical, social and cultural perspectives.…”
Section: Introductionmentioning
confidence: 97%